William James, Pragmatism, and American Culture - Whitehead, Deborah (Book collections on Project MUSE., 2015)
William James, Pragmatism, and American Culture focuses on the work of William James and the relationship between the development of pragmatism and its historical, cultural, and political roots in 19th-century America. Deborah Whitehead reads pragmatism through the intersecting themes of narrative, gender, nation, politics, and religion. As she considers how pragmatism helps to explain the United States to itself, Whitehead articulates a contemporary pragmatism and shows how it has become a powerful and influential discourse in American intellectual and popular culture.--Provided by publisher.